THE EFFECT OF USING GIST (GENERATING INTERACTION BETWEEN SCHEMATA AND TEXT) STRATEGY ON STUDENTS’ READING COMPREHENSION - Mona Rizkia Pebriani; Nani Ronsani Thamrin; Endang Darsih; Fahrus Zaman Fadhly (Indonesian Journal of Learning and Instruction, 2022)
This research focused on GIST (Generating Interaction between Schemata and Text) strategy in increasing students’ reading comprehension. The objective of the research is to find out the significant effect on students’ reading comprehension after applying the GIST (Generating Interactions between schemata and text) strategy. This research used a quasi-experimental design. The sample consists of 60 students which were from two classes. This research used test instrument (pre-test and post-test) with multiple choice questions. The hypothesis was calculated by using t-test in which the analysis result obtained tcount = 4.33 > ttable = 2.00 with α = 0.05. From the result, it can be concluded that GIST strategy can improve students’ reading comprehension in narrative text. Keywords: Generating Interaction between Schemata and Text (GIST) strategy; reading comprehension; narrative text.